2021
DOI: 10.21037/tau.2020.03.35
|View full text |Cite
|
Sign up to set email alerts
|

Histology and sperm retrieval among men with Y chromosome microdeletions

Abstract: In this review of Y chromosome microdeletions, azoospermia factor (AZF) deletion subtypes, histological features and microTESE sperm retrieval rates are summarized after a systematic literature review. PubMed was searched and papers were identified using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Approximately half of infertile couples have a male factor contributing to their infertility. One of the most common genetic etiologies are Y chromosome microdeletions. Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 96 publications
1
22
0
3
Order By: Relevance
“…However, the initial diagnosis of the patients in our cohort was NOA. In most patients who had genetic, or other causes besides Klinefelter, the gonadotropin, testosterone and PRL values were almost at the same level as those in our NO‐IA group (Ly et al, 2021; Yuen et al, 2021). In Klinefelter patients, intermittent azoospermia was detected mostly in mosaic types aged 13–24 years.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the initial diagnosis of the patients in our cohort was NOA. In most patients who had genetic, or other causes besides Klinefelter, the gonadotropin, testosterone and PRL values were almost at the same level as those in our NO‐IA group (Ly et al, 2021; Yuen et al, 2021). In Klinefelter patients, intermittent azoospermia was detected mostly in mosaic types aged 13–24 years.…”
Section: Discussionsupporting
confidence: 71%
“…Generally, reference was made to patients who initially displayed severe oligospermia or CO associated with genetic factors (Klinefelter, partial deletion, etc.) and in whom azoospermia developed and intermittent ejaculate was detected in their spermatozoa (Ly et al, 2021; Yuen et al, 2021). The difference in these patients compared with our cohort was that they had spermatozoa in their ejaculate when diagnosed with infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently deleted locus in infertile men is AZFc (60–70%), followed by AZFa (0.5–4%), AZFb (1–5%) and AZFb+c (1–3%) deletion [ 10 ]. Men with complete AZFa and AZFb deletions are azoospermic, and sperm cannot be surgically retrieved [ 11 ]. A study reported that 3 out of 15 patients with AZFb deletions had sperm on mTESE [ 12 ]; however, the Authors defined the AZFb deletions using sY127 and sY134 marker, while classically, the AZFb locus is proximally defined by sY108 and distally characterized by sY134 or sY135; therefore, a partial AZFb deletion could not be excluded in such cases.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…A study reported that 3 out of 15 patients with AZFb deletions had sperm on mTESE [ 12 ]; however, the Authors defined the AZFb deletions using sY127 and sY134 marker, while classically, the AZFb locus is proximally defined by sY108 and distally characterized by sY134 or sY135; therefore, a partial AZFb deletion could not be excluded in such cases. Men with complete AZFc deletions may have sperm in the ejaculate or be azoospermic, but with good chances of SSR: a recent review reporting the results of 32 studies found that sperm could be retrieved in 13 to 100% of cases, particularly when mTESE was used [ 11 ]. Thus, AZFc deletion may confer better chances of SSR to patients with NOA.…”
Section: Clinical Factorsmentioning
confidence: 99%